Mortal [videorecording (DVD)] - Paus, Marcus (Saban Films / Lionsgate, 2020)
A sleepy Norwegian town erupts after an American backpacker is arrested. Witnesses claim a teen died after touching the stranger, and that he inexplicably started a fire that engulfed a farm. He warns a psychologist, Christine, that he has supernatural powers, and that anyone who gets too close to him dies. Is he a liar, a freak of nature, an angry god? Determined to find the truth, Christine draws nearer, and what she finds is beyond her wildest imaginings.